DIGITIZATION AND ITS IMPACT ON THE QUALITY OF HIGHER EDUCATION IN ALGERIAN UNIVERSITIES - Boutarfa Rochdi; Zedira Khammar (International Journal of Innovative Technologies in Social Science, 2024)
This study aims to shed light on the reality of digitalization in higher education institutions, by exploring the strategies of the relevant ministry. These strategies include developing a framework for operationalizing the principles of digitalization and digital transformation, as well as identifying platforms and programs used to promote education and learning. The study also highlights the role of these tools in enabling researchers to effectively perform their tasks, keep abreast of developments in scientific research methods, and benefit from digitalization technology, which can help strengthen innovation and improve the quality of scientific research. It should be added that this study also aims to analyze the challenges faced by higher education institutions in implementing digitalization strategies and to formulate practical recommendations to improve the teaching and research process.